Alpine steppe vegetation communities are more sensitive to plateau pika disturbance than alpine meadows - Hua, Rui; Zhang, Peng; Wang, Liqing; Huang, Miaomiao; Hua, Limin; Zhou, Jianwei (Frontiers in Plant Science, 2025)
IntroductionSmall herbivores are important biological factors affecting plant productivity and species richness in the grassland ecosystem of the Tibetan Plateau. However, the response of different grassland types to the disturbance of the “endemic species” plateau pika (Ochotona curzoniae) remains unclear.MethodsIn this study, two representative grassland types, alpine meadow and alpine steppe, were taken as research objects to compare the effects of pika disturbance on vegetation structure and function indicators, and to explore the disturbance response threshold of these ecosystems.ResultsThe results showed that the alpine steppe was more sensitive to pika disturbance, with significant decreases in biomass, vegetation height, and coverage even at low disturbance levels. In contrast, alpine meadows exhibited greater resilience, maintaining higher productivity and species diversity under moderate disturbance conditions. Notably, the functional index of alpine meadow peaked under moderate disturbance, while alpine steppe rapidly transitioned to a degraded state. These differences highlight the varying disturbance thresholds between the two grassland types.DiscussionThis study highlights the vulnerability of alpine grassland ecosystems to pika disturbance and provides a strong scientific basis for designing effective grassland management and ecological restoration strategies.